Obesity and related comorbidities in a large population-based cohort of subjects with type 1 diabetes in Catalonia - Genua, Idoia; Franch-Nadal, Josep; Navas, Elena; Mata-Cases, Manel; Giménez-Pérez, Gabriel; Vlacho, Bogdan; Mauricio, Didac; Goday, Albert (Frontiers in Endocrinology, 2022)
BACKGROUND: Obesity, an increasing global health problem, can affect people with other disease conditions. The prevalence of obesity in people with type 1 diabetes (T1D) is not well known. The aim of this study was to describe extensively the characteristics and prevalence of different classes of obesity according to BMI (body mass index) categories in a large cohort of patients with T1D. MATERIAL AND METHODS: This was a retrospective, cross-sectional study in Catalonia. We reviewed all patients with T1D diagnosis, ≥ 18 years old and with BMI data from the SIDIAP database. Sociodemographic and clinical data, cardiovascular risk factors, laboratory parameters and concomitant medications were collected. RESULTS: A total of 6,068 patients with T1D were analyzed. The prevalence of obesity in the total sample was 18% (13.8% with class 1 obesity [BMI 30-34.9 kg/m2]). Patients with obesity had a higher prevalence of other cardiovascular risk factors (i.e. hypertension was 61.4% vs. 37.5%; dyslipidemia 63.6% vs 44%, and chronic kidney disease 38.4% vs. 24.4%; p<0.001 in all cases) and poorer control of them. The higher prevalence was regardless of sex, age and duration of diabetes. The increase in these comorbidities was noticeable from a BMI > 25 kg/m2. Patients with obesity did not have poorer glycemic control. CONCLUSION: The presence of obesity in people with T1D is frequent and cardiovascular risk factors are more common and more poorly controlled in T1D patients with obesity.